Pengaruh Disiplin Kerja dan Kemampuan Kerja Terhadap Prestasi Kerja Karyawan - Muhammad Arif; Taufik Maulana; Muhammad Taufik Lesmana (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
The purpose of this study was to determine and analyze the effect of work discipline on employee performance, to know and analyze the effect of work ability on employee work performance and to find out and analyze the effect of work discipline and work ability on employee performance in PT Perkebunan Nusantara III Medan. The population in this study all permanent employees totaling 197 people taking, where sampling using slovin formula with a total sample of 66. Data collection techniques used in this study were documentation, interviews and questionnaires. The analysis techniques used in this study are multiple regression, classic assumptions, hypothesis testing and coefficient of determination. The conclusion of this study proves that Work Discipline has a significant effect on Employee Performance at the Office of the Directors of PT Perkebunan Nusantara III Medan, Work Ability has a significant effect on Employee Performance at the Office of Directors of PT Perkebunan Nusantara III Medan and Simultaneously Work Discipline and Work Ability have a significant effect on Employee Performance in the Office of the Directors of PT Perkebunan Nusantara III Medan, which can be categorized as strong.